The Influence of Mobile Banking, Internet Banking, and Automated Teller Machine (ATM) Transactions on Fee Based Income - Haryanto, Lenawati; Septiawan, Irsyad (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research aims to determine the effect of Mobile Banking, Internet Banking, and Automated Teller Machine (ATM) on Fee Based Income. It is hoped that this research can contribute and explain the factors that influence fee-based income for conventional banking companies on the Indonesian Stock Exchange. The objects of this research are Mobile Banking, Internet Banking, and ATM as independent variables and Fee based income as the dependent variable. The subject of this research is conventional banks listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The research sample consisted of 5 (five) banks, namely Bank Mandiri, Bank Negara Indonesia (BNI), Bank Central Asia (BCA), Bank CIMB Niaga, and Bank Mega. Data analysis using multiple regression using the SPSS 22 application. Research findings that Mobile Banking, Internet Banking and ATM together have a significant effect on Fee based income. There is a positive influence of Mobile Banking on Fee Based Income but there is no influence of Internet Banking on Fee based income. This indicates that the large number of Internet Banking users tends not to increase the bank's Fee Based Income. There is a positive and significant influence of ATMs on Fee based income, this indicates that the more customers who make transactions using ATMs, the greater the Bank's Fee based income will increase.